The prevention of weight regain in bariatric surgery patients at Counties Manukau Health : a thesis completed as part of the requirements for Master of Science in Nutrition and Dietetics at Massey University, Albany Campus Auckland, New Zealand - Billing-Bullen, Gypsy (Massey University, 2019)
Background: Weight-regain is commonly experienced post-bariatric surgery. This study aimed to assess the impact of a structured eating behaviour group education programme on food intake and eating behaviours which contribute to weight regain. Methods: Participants (n=41) were adults at least 12-months post-bariatric-surgery, recruited through CM Health over six months, representing gender and ethnic diversity. This study evaluated whether the current dietitian-led group education session at 18- months resulted in changes to weight, body composition, quality of life, food intakes and/or eating behaviours. There was also an additional 21-month group session added, which involved a focus group to explore barriers and enablers related to weight management during the bariatric journey. Quantitative measures included body composition analysis using bioelectrical impedance, dietary and eating behaviour measures were conducted utilising validated questionnaires, and data was analysed with Wilcoxin, and Paired T-tests. Thematic analysis was used to evaluate the focus group investigations of participant (n=28) experiences. Results: There were no significant changes in body composition, eating behaviours, and energy or nutrient intakes in the three-day WFRs between 18 and 21-months post- surgery, but food variety scores significantly increased from 51.0 to 59.29 (p= 0.032). Flesh food intakes significantly increased from 2.50 to 7.50 per week between 18 and 21-months, as did savoury snack foods (1.50 to 2.0 per week, p <0.001). Quality of life significantly decreased at 18 and 21-months, compared to 12-months post-surgery (1.91, 0.95, 0.99, respectively, p= 0.002). Thematic analysis revealed five key themes: a life changing health journey, barriers to following a healthy lifestyle, challenges to changing eating behaviour, mindset changes and requiring ongoing support. The focus groups also identified that the participants desired more support throughout the bariatric program. Conclusion: Thematic analysis identified the group education programme was found valuable, providing patients with increased support post-surgery from dietitians and peers. These findings provide important insights into the challenges bariatric patients face and key learnings to develop specific supports in the future. Although quantitative improvements to eating behaviours were not found, some areas of dietary quality improved.
Keywords: Obesity; Surgery; Patients; New Zealand; Auckland; Attitudes; Weight gain; Prevention; Food habits; 321004 Nutritional science